Pendampingan Implementasi Sistem Informasi Desa Untuk Meningkatkan Efisiensi Pelayanan Administrasi Dan Tata Kelola BUMDes - Manrejo, Sumarno; Ningrum, Endah Prawesti; Priatna, Wowon; Hernowo, Pandit; Pasaribu, Ahmad Muchlisin Natas; Endah Prawesti Ningrum (Jurnal Pengabdian kepada Masyarakat UBJ, 2025)
Digital transformation at the village level is essential to improve the efficiency of public services and strengthen local economic management. However, many villages still rely on manual administrative processes and conventional business management systems for Village-Owned Enterprises (BUMDes). This community service activity aimed to implement a Smart Village application integrated with BUMDes management in Neglasari Village, Sumedang Regency. The program was carried out through several stages, including socialization, training, technology implementation, mentoring, and evaluation. The implemented system integrates three main components: digital village administration services, integrated BUMDes and MSME management, and digital promotion of village products. The results show that the application improved administrative service efficiency, reducing service time from 15–20 minutes to 5–7 minutes per request. In addition, the system reduced administrative recording errors and enabled real-time monitoring of BUMDes transactions and financial reports. Training activities also increased participants' understanding of system usage, with an average score of 4.3 on a five-point scale. Overall, the implementation of the Smart Village application contributes to improving service efficiency, strengthening village business management, and supporting sustainable digital transformation in Neglasari Village